PRELIMINARY IN VITRO ANTISICKILNG PROPERTIES OF CRUDE JUICE EXTRACTS OF PERSIA AMERICANA, CITRUS SINENSIS, CARICA PAPAYA AND CIKLAVIT®. - Iweala, E. E.; Uhegbu, F. O.; Ogu, G. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The antisickling properties of crude juice extracts of the edible portions of three commonly consumed tropical fruits namely Persia americana, Citrus sinensis, and Carica papaya were investigated in vitro alongside a new drug preparation called Ciklavit® that has antisickling activity. Four different solvent extracts of the crude juice of each fruit including aqueous, acidic, alkaline and alcoholic extracts were prepared and their antisickling effects on sickle cell trait (HbAS) and sickle cell disease (HbSS) blood samples checked alongside Ciklavit®. Blood samples were stabilized using normal saline and the antisickling effects were checked by counting the number of sickle cells remaining after incubation of the blood samples with the crude fruit extracts and Ciklavit® for twenty-four hours. The results showed that Ciklavit® produced a sustained reduction in the number of sickle cells in both HbAS and HbSS blood samples. Also the alkaline and alcoholic extracts of P. americana and C. papaya produced significant reduction in the number of sickle cells.